Parameter synthesis for hierarchical concurrent real-time systems - ANDRÉ, Étienne (Institutional Knowledge at Singapore Management University, 2012)
Modeling and verifying complex real-time systems, involving timing delays, are notoriously difficult problems. Checking the correctness of a system for one particular value for each delay does not give any information for other values. It is hence interesting to reason parametrically, by considering that the delays are parameters (unknown constants) and synthesize a constraint guaranteeing a correct behavior. We present here Parametric Stateful Timed CSP, a language capable of specifying hierarchical real-time systems with complex data structures. Although we prove that the synthesis is undecidable in general, we present an algorithm for efficient parameter synthesis that behaves well in practice.